Myths and Gender Relations in Short Stories When Mothers Come by Dwi Ratih Ramadhany - Ariani, Ni Komang (IJLHE: International Journal of Language, Humanities, and Education, 2025)
The short story "When Mother Comes" by Dwi Ratih Ramadhany presents the figure of a mother from three generations who has to grapple with dilemmas in her life, which then shows the gender relations between the characters. Dwi Ratih Ramadhany who is a female writer born in Sampang, Madura who raises many female themes in her work. The short story "When Mother Comes" is told through a simple plot through the arrival of a mother to her child's house, when her child gives birth. This study concludes that there are a number of myths that the Mother character brings as the old generation, to the I, as the new generation. These myths include the myth of 'fighting the mother makes the child go to hell', the myth of 'the baby's urine is put in a jug', the myth 'the breast is infested with jinn and demons so that the child does not want to breastfeed'. Meanwhile, the gender relations that emerge in this short story are divided into two, the first is that perpetuates gender stereotypes, namely, associating domestic tasks with female characters, demonizing female characters as grumpy monsters, positioning male characters as more rational parties in the midst of the absence of these characters in family debates, while the second is breaking gender stereotypes seen in the “I” character who has agency and critical power to question the gender stereotypes imposed on her.